Meningkatkan Aktivitas dan Keterampilan Berpikir Kritis Menggunakan Model PANTING pada Siswa Kelas V (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2023)
This study addresses the issues of low activity, critical thinking skills, and learning outcomes in science class. The objective is to describe the analysis of teacher and student activities and to analyze the improvement of critical thinking skills and learning outcomes. The research uses Classroom Action Research (CAR) conducted over four meetings in a fifth-grade class consisting of 18 students, 8 male and 10 female, at SDN Danda Jaya 3. Qualitative data was obtained through observation of teacher and student activities, as well as student critical thinking skills. The results indicate that the teacher's activities in meetings 1 to 4 were well-implemented. Student activities improved from 44% to 94% throughout meetings 1 to 4, almost entirely meeting the criteria for being active. Student critical thinking skills also improved from 39% to 94% over meetings 1 to 4, meeting almost all criteria for being skilled. The level of student learning outcomes increased from 44% to 100%. Based on the findings, the PANTING teaching model can improve student activity and critical thinking skills.